2016
DOI: 10.1111/imj.13098
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome as a complication of chronic graft‐versus‐host disease after allogeneic haemopoietic stem cell transplantation

Abstract: Nephrotic syndrome (NS) is a rare complication following allogeneic haemopoietic stem cell transplantation (allo-HSCT), with limited current understanding of its pathogenesis. Here, we describe four cases of NS following allo-HSCT diagnosed at our institutions to identify key clinical and pathological features. In addition, a PubMed search was performed to identify existing reports that were pooled together with our cases for analysis. NS occurred as a late complication following allo-HSCT, with median onset 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets. [5][6][7] In MCD, T cell activation may be the cause of cytokine and antibody-mediated injury and can occur without other signs of GVHD, as evidenced in our patient. 8,9 The largest series of NS after GVHD was published by Reddy et al 10 who followed 889 patients and evaluated who developed non-cardiac edema with only 9 patients (0.9%) having evidence of NS.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets. [5][6][7] In MCD, T cell activation may be the cause of cytokine and antibody-mediated injury and can occur without other signs of GVHD, as evidenced in our patient. 8,9 The largest series of NS after GVHD was published by Reddy et al 10 who followed 889 patients and evaluated who developed non-cardiac edema with only 9 patients (0.9%) having evidence of NS.…”
Section: Discussionsupporting
confidence: 53%
“…Minimal change disease was found in 15% of reports. 6 Similarly, Cho et al 7 reported in his cohort MN was the common glomerulopathy post HSCT. Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets.…”
Section: Discussionmentioning
confidence: 78%
“…A study by Chang et al [34]-to our knowledge, the largest reported cohort of indication biopsies to date, with 20 patients-showed similar frequencies, with TMA and membranous glomerulonephritis among the more common diagnoses. On the other hand, these authors reported 3 cases of minimal change disease, another putative pattern of chronic GVHD [35]. They also presented 3 cases of polyoma virus nephropathy, which was also not present in our cohort.…”
Section: Discussioncontrasting
confidence: 52%
“…Additionally, renal manifestations of both acute and chronic graft versus host disease (GvHD) have been described, including nephrotic syndrome, which usually occurs as a late complication most commonly due to membranous nephropathy. [2][3][4] Post-transplant lymphoproliferative disorder (PTLD) post HSCT occurs in up to 3.2% of allogeneic transplant recipients and is almost exclusively Epstein Barr virus (EBV) related. 5 Management includes reduction of immunosuppression, Rituximab and or chemotherapy in higher risk disease.…”
Section: Introductionmentioning
confidence: 99%